Collybiopsis baiyunensis sp. nov. (Omphalotaceae, Agaricales) from Baiyun Mountain, Southern China - Liu, Xiao-Chun; Lin, Zhi-Jun; Liang, Ying-Shan; Cao, Li-Xiang; Qiu, Li-Hong (Phytotaxa, 2024)
Collybiopsis baiyunensis, a new species collected from Baiyun Mountain, Guangzhou, Southern China, is described based on phylogenetic analyses of combined ITS and nrLSU sequences and morphological evidence. It is characterized by its light brown to yellowish brown pileus with reddish orange to reddish brown disc and whitish margin, oblong to subcylindrical basidiospores, clavate to broadly clavate or spheropedunculate cheilocystidia, absence of pleurocystidia, and cylindrical or flexuose caulocystidia. Detailed morphological descriptions, phylogenetic analyses and comparisons with closely related species are presented.